Modulatory effect of high saturated fat diet-induced metabolic disturbances on angiogenic response in hepatocyte RXRα knockout mice - RaŹny, Urszula (2010)
Metabolic syndrome and diabetes lead to pathological angiogenesis and angiopathy. Metabolic disturbances occur as an effect of genetic and environmental interaction. Hyperleptinemia accompanies obesity and leptin is a potent proangiogenic factor. The aim of the study was to investigate the effect of high fat diet-induced alterations in gene expression and angiogenic response in the hRXRα ko mice lacking of hyperglycemia. hRXRα ko and control mice were fed either standard or high saturated fat (HF) diet for 7 weeks. Body weight and biochemical parameters (glucose, triglycerides, cholesterol), insulin and adipokines (leptin, adiponectin) were monitored. At sixth week of feeding, mice were subcutaneously injected for 6 days with matrigel containing bFGF. Then, matrigel plugs were used for immunohistochemical staining of cells with CD31 antibody and gene expression assessment (by microarray confirmed for some genes with quantitative real time PCR). For description of angiogenesis CD31 positive structures were counted in the matrigel sections. HF diet feeding of the hRXRα ko mice resulted in increased serum cholesterol and leptin level and in tendency to decrease angiogenesis (number of vessels with lumen). The microarray studies revealed that HF diet down-regulated genes related to angiogenesis (Nos3, Kdr) and up-regulated genes connected with apoptosis (activators of caspase 3, proapoptotic genes Bcl2) and proinflammatory pathway (NfκB pathway, Tnfα). Summing up, HF diet feeding of hRXRα ko mice resulted in dyslipidemia and hyperleptinemia as well as impaired angiogenic response, and cell apoptosis. These results argue for independent participation of dyslipidemia and hyperleptinemia in pathology of angiogenic response associating metabolic syndrome.